1999
DOI: 10.1063/1.123362
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of x-ray photoelectron spectra of elastic amorphous carbon nitride thin films

Abstract: We report the synthesis and characterization of amorphous carbon nitride (CNx) thin films using a direct current magnetron reactive sputter system. Nanoindentation of the CNx films and amorphous carbon films deposited under similar conditions shows the CNx films are extremely elastic, that the addition of nitrogen fundamentally changes the mechanical properties of the films, and that traditional methods of calculating the hardness and Young’s modulus may not be valid. X-ray photoelectron spectroscopy (XPS) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 10 publications
2
26
0
Order By: Relevance
“…Since the amorphous carbon contacting with the metal phases can graphitize at relatively low temperature and the high kinetic energy of the sputtered C species can locally heat the amorphous carbon on the metal phases according to a thermal spike model, it is expected that a local increase in the sp 2 bonds in the amorphous carbon structure is due to metal-induced graphitization [21][22][23]. It is also reported [4,8,19,[24][25][26][27] that nitrogen doping in DLC films forms new sp 2 sites and encourages the sp 2 sites to cluster because of preferential π bonding of nitrogen. Therefore, the increased carbon sputtering power should cause a decrease in the number of the sp 2 bonds in the PtRuN-DLC films via the decreased Pt, Ru and N contents in the films (Fig.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Since the amorphous carbon contacting with the metal phases can graphitize at relatively low temperature and the high kinetic energy of the sputtered C species can locally heat the amorphous carbon on the metal phases according to a thermal spike model, it is expected that a local increase in the sp 2 bonds in the amorphous carbon structure is due to metal-induced graphitization [21][22][23]. It is also reported [4,8,19,[24][25][26][27] that nitrogen doping in DLC films forms new sp 2 sites and encourages the sp 2 sites to cluster because of preferential π bonding of nitrogen. Therefore, the increased carbon sputtering power should cause a decrease in the number of the sp 2 bonds in the PtRuN-DLC films via the decreased Pt, Ru and N contents in the films (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…Therefore, the improved adhesion strength of the PtRuN-DLC films with increased carbon sputtering power lowers the friction of the films by preventing the delamination of the films during the sliding. In addition, the increased graphitization of the PtRuN-DLC films with increased carbon sputtering power should be one of the reasons decreasing the friction of the films since the lubricating effect resulted from the graphitic clusters reduces the friction of the films [26,31,36,48].…”
Section: Resultsmentioning
confidence: 99%
“…N atoms present in the disordered matrix and at the border of aromatic clusters (in both cases contributing to P1) favor the inter-link between graphitic planes. This is possible by either directly connecting two adjacent planes [13] or by inducing a higher reactivity in the surrounding C atoms [3]. On the other hand, substitutional nitrogen atoms in graphitic clusters supply pdoping electrons.…”
Section: Discussionmentioning
confidence: 98%
“…It was reported that doping of non-metals, such as nitrogen (N), etc., resulted in the enhanced adhesion strength of DLC films by increasing sp 2 bonds and subsequently relaxing residual stress in the films [4,5,14,[16][17][18]. In addition, the tribological performance of DLC films can be improved by N 318 Friction 2(4): 317-329 (2014) doping because the incorporation of N in DLC films promotes the graphitization of the films and reduces the friction of the films via the enhanced lubricating effect [19][20][21][22]. It is expected that co-incorporation of Pt, Ru and N in DLC films could improve the adhesion strength and tribological performance of the PtRuN-DLC films for micromold applications.…”
Section: Introductionmentioning
confidence: 99%